2020
DOI: 10.1186/s13075-020-02242-8
|View full text |Cite
|
Sign up to set email alerts
|

High susceptibility to collagen-induced arthritis in mice with progesterone receptors selectively inhibited in osteoprogenitor cells

Abstract: Background: Progesterone receptor (PR) affects immunomodulation, and lack of PR in osteoprogenitor cells primarily affects pathways associated with immunomodulation, especially in males. In this study, we selectively deleted PR from osteoprogenitor cells using Prx1-Cre to evaluate the tissue-specific effects of PR on the pathegenesis of inflammatary arthritis (IA). Methods: Collagen-induced arthritis (CIA) was used as an IA animal model. Both male and female PR ΔPrx1 mice and their wild-type (WT) littermates w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In the same CIA model, it has also been reported that mice with deletion of a P4 receptor allele in osteoprogenitor cells (PR DPrx1-CIA) have a greater incidence of osteoarthritis. Male mice have lower bone mass in the legs and knees, a lower volume of subchondral trabecular bone and greater erosion and damage to the cartilage of the knee joint (167). Therefore, P4 plays a protective role in the manifestations of RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In the same CIA model, it has also been reported that mice with deletion of a P4 receptor allele in osteoprogenitor cells (PR DPrx1-CIA) have a greater incidence of osteoarthritis. Male mice have lower bone mass in the legs and knees, a lower volume of subchondral trabecular bone and greater erosion and damage to the cartilage of the knee joint (167). Therefore, P4 plays a protective role in the manifestations of RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%